Strategi Pembelajaran PAI Berbasis Literasi dalam Meningkatkan Pemahaman Keislaman Siswa - Ryanxxa Delno Dinata; Gunawan Fauzi; Gusmaneli Gusmaneli (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to explore the strategy of literacy-based learning in Islamic Religious Education (IRE) to enhance students' understanding of Islam. Through a literature review approach, this research analyzes various sources related to the implementation of literacy in IRE teaching and its impact on students' comprehension of Islamic teachings. The findings indicate that literacy-based learning enhances students' critical skills in understanding religious texts and enriches their understanding of Islam in a practical context. Moreover, this strategy plays a key role in character building, fostering moral values, raising social awareness, and improving communication skills. The teacher's role as a facilitator guiding students in developing religious literacy skills is also crucial for the success of this approach. This study aims to contribute to the development of a more relevant and effective IRE teaching model in the digital era.